A pirate's life for tea - Thorne, Rebecca, 1991- (Thorne, Rebecca, 1991- Tomes and tea novel ;, 2024)
"Kianthe and Reyna are on the hunt for dragon eggs to save their hometown but it requires making a deal with Diarn Arlon, lord of the legendary Nacean River. Simply capture the river pirate Serina, who's been plaguing Arlon's supply chains, and bring her in for justice. Easy peasy. Begrudgingly, the couple joins forces with Bobbie, one of Arlon's constables determined to capture the pirate. Except Bobbie and Serina have a more complicated history than anyone realized, and it might jeopardize everything." -Back cover